Neural Correlates of Phrase Rhythm: An EEG Study of Bipartite vs. Rondo Sonata Form - Martínez-Rodrigo, Arturo; Fernández-Sotos, Alicia; Latorre, José Miguel; Moncho-Bogani, José; Fernández-Caballero, Antonio (Frontiers in Neuroinformatics, 2017)
This paper introduces the neural correlates of phrase rhythm. In short, phrase rhythm is the rhythmic aspect of phrase construction and the relationships between phrases. For the sake of establishing the neural correlates, a musical experiment has been designed to induce music-evoked stimuli related to phrase rhythm. Brain activity is monitored through electroencephalography (EEG) by using a brain-computer interface. The power spectral value of each EEG channel is estimated to obtain how power variance distributes as a function of frequency. Our experiment shows statistical differences in theta and alpha bands in the phrase rhythm variations of two classical sonatas, one in bipartite form and the other in rondo form.